ANALYSIS OF LOCAL BUCKLING PROPAGATION FOR DEEP WATER PIPELINES - SURJITO ( NIM : 13104100); Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, PRIYATNO
Local buckling in the offshore pipeline due to external pressure or other causes will be propagate when hidrostatik sea water pressure is high enough. Analysis is conducted to calculate minimum wall thickness of pipe that so propagation buckling does not occur. Minimum wall thickness calculation was conducted based on DnV OS F101, API RP 1111, and BS 8010. To simplify the analysis, the author developed program for the calculation (calculation sheet) using Microsoft Office Excel. To understand the influence of the several main calculation parameters is done the analysis parameters calculation, the results are shown in the form of graphs. As a case study, the author analyzes field Sadewa W to Attaka platform and West seno development field phase II pipeline. From the results of the analysis for the conditions obtained for the installation of pipeline Sadewa W to Attaka platform with a diameter 8 in required 0,25 in wall thickness and the diameter of pipe 16 in need 0,5 in wall thickness. Pipeline for the West Seno field development phase II, with 12.75 in diameter required 0,84 in wall thickness. Analysis of collapse pressure and propragation pressure is also conducted for various level degradation of wall thickness. Collpase pressure will exceed collapse criteria when ratio of corrosion depth and initial wall thickness for pipe 8 in is 43,5%, pipe 16 in is 49%, and pipe 12 in is 41%.